Balancing Accuracy and Simplicity in Determining Reorder Points - Hunt, Joseph A. (Management Science, 1965)
Many methods have been developed to determine the proper reorder points and order quantities in an inventory system. These methods are based on a wide range of inventory models—from elementary deterministic models to sophisticated probabilistic models with time-varying parameters. This paper deals with two topics related to these calculations which were encountered during the design of an inventory control system for a firm in the heavy goods industry. A mathematical model is developed to describe the average annual variable cost of maintaining the inventory. Based on this model, the paper evaluates the savings obtained by using a simultaneous solution for reorder point and order quantity rather than a simpler separate solution. Then, this model is extended to describe the effect of batch withdrawals as a renewal process. The paper presents an adjustment which can be applied to the original reorder points based on unit withdrawals. Both of these topics are described in the context of a practical application.